Pendapatan dan Persepsi Anggota terhadap Penerapan Internal Control System pada Pertanian Padi Organik - Netra Mirawati; Aris Munandar; Sapta Raharja (Institut Pertanian Bogor, 2014)
Internal Control System (ICS) is a consolidated management concerning the effort to certify organic products. Due to its collective mechanism, farmers are able to manage its agribusiness more profitably financially. The purpose of this study was (1) to analyze the differences in income levels of farmer groups who are certified organic and non-certified organic, (2) to get an overview of the implementation of ICS in farmers group Gapoktan Simpatik, and (3) to analyze the perceptions of group members towards the implementation of ICS either certified or non-certified organic. This research was on a case study at upper stream of Cideres and Cigunungjaga watershed in the district of Sukahening, Tasikmalaya, which is a member of Gapoktan Simpatik. The analysis was performed using the R/C ratio, homogeneity analysis of data by income level using the Kolmogorov-Smirnov, analysis of income differences between the two groups of independent farmers using the Mann-Whitney test, and biplot analysis for the analysis of perceptions of group members toward ICS implementation variables. The results showed that the R/C ratio for the certified group was 1.77, and for non-certified group 1.53. The average income level of certified group was Rp19,394,800/ha/year, while the non-certified Rp12,728,940/ ha/year. The results also showed that perception toward ICS implementation of certified group was better than the non-certified. Most of the certified group respondent approached the vector of all variables, which means that they were satisfied and familiar with all the variables, while the group of respondents who were non-certified did not approach the vector. The parameters that were widely varied by respondent group responses were the certified variable of purchase, handling, processing, and export, while the most uniform response variables of the respondents were variable of organizational and ICS personnel. While the groups that were not certified provided a variety of assessment on the variables of risk management and uniform assessment on external inspection and certification.